Impact of maize conservation agricultural system on nitrogen losses through surface runoff and soil erosion in dryland - Fitri Wijayanti; Syahrul Kurniawan; Didik Suprayogo (Journal of Degraded and Mining Lands Management, 2019)
Nutrient loss in dry land through surface runoff and soil erosion is thought to dominate the watershed eutrophication. Conservation agriculture is expected to be able to reduce the nitrogen (N) loss into river systems. This study aimed to compare the N total input between conservation and conventional farming systems and to analyze N losses through surface runoff and soil erosion in conservation agriculture compared to conventional farming systems. The study was conducted at Agro-Techno-Park at Jatikerto, Brawijaya University from December 2017 to September 2018. The experiment was designed with three factors, i.e. (1) with and without biogeotextile, (2) No and conventional tillage, (3) application of four kinds of cover crop residues, with three replications. Results of the study showed that conservation agriculture was able to provide higher N inputs into the soil than conventional agriculture. The N loss through surface runoff was relatively low, ranging from 0.03 kg/ha to 0.45 kg/ha. N loss through erosion with conventional tillage and without biogeotextile reached 15 kg/ha to 32 kg/ha. No-tillage practices combined with the biogeotextile application significantly reduce N losses through soil erosion to only 0.3 kg/ha to 5 kg/ha. Conservation agriculture is one of the solutions to overcome the trade-off between the need for increased food production and environmental protection.